Aesthetic Concepts and Interdisciplinary Approach in a Patient With Bilateral Cleft Lip and Palate and Missing Premaxilla: A Case Report. (August 2021) - Abreu, Amara; Londono, Jimmy; Torosian, Aram; Yu, Jack; Levy-Bercowski, Daniel
The smile is an important part of the individual's facial expression, it allows the communication of emotions and ideas. However, its aesthetics can be severely compromised in patients with cleft lip and palate due to multiple missing, malformed and malposed teeth, abnormal soft tissue morphology, upper lip scar tissue, and altered anatomy in the lower third of the face. This clinical case reports the interdisciplinary treatment approach of a young male patient with complete bilateral cleft lip and palate and missing premaxilla. Prosthodontic rehabilitation included a zirconia-based fixed dental prosthesis, with pink porcelain to camouflage the bony defect and restore the facial and dental aesthetics. Maxillary second premolars received lithium disilicate crowns to obtain a more harmonious smile line and adequate occlusion. A resin-bonded fixed partial denture restored a missing mandibular central incisor. Tooth proportions, gingival contours and facial ratios routinely used in noncleft patients, were used to achieve a consonant smile. The final restorations satisfied the patient's expectations, restored an aesthetically pleasant smile, and provided an adequate occlusion.